Structural and environmental controls on Antarctic ice shelf rift propagation inferred from satellite monitoring. Issue 4 (13th November 2013) - Walker, C. C.; Bassis, J. N.; Fricker, H. A.; Czerwinski, R. J.
<x xml:space="preserve">Abstract</x> [1] Iceberg calving from ice shelves accounts for nearly half of the mass loss from the Antarctic Ice Sheet, yet our understanding of this process is limited. The precursor to iceberg calving is large through‐cutting fractures, called "rifts, " that can propagate for decades after they have initiated until they become iceberg detachment boundaries. To improve our knowledge of rift propagation, we monitored the lengths of 78 rifts in 13 Antarctic ice shelves using satellite imagery from the Moderate Resolution Imaging Spectroradiometer and Multiangle Imaging Spectroradiometer between 2002 and 2012. This data set allowed us to monitor trends in rift propagation over the past decade and test if variation in trends is controlled by variable environmental forcings. We found that 43 of the 78 rifts were dormant, i.e., propagated less than 500 m over the observational interval. We found only seven rifts propagated continuously throughout the decade. An additional eight rifts propagated for at least 2 years prior to arresting and remaining dormant for the rest of the decade, and 13 rifts exhibited isolated sudden bursts of propagation after 2 or more years of dormancy. Twelve of the fifteen active rifts were initiated at the ice shelf fronts, suggesting that front‐initiated rifts are more active than across‐flow rifts. Although we did not find a link between the observed variability in rift propagation rate and changes in atmospheric temperature or sea ice concentration correlated with, we did find a statistically significant correlation between the arrival of tsunamis and propagation of front‐initiated rifts in eight ice shelves. This suggests a connection between ice shelf rift propagation and mechanical ocean interaction that needs to be better understood.